2022
DOI: 10.1111/trf.16968
|View full text |Cite
|
Sign up to set email alerts
|

The Norwegian blood preparedness project: A whole blood program including civilian walking blood banks for early treatment of patients with life‐threatening bleeding in municipal health care services, ambulance services, and rural hospitals

Abstract: Background Civilian and military guidelines recommend early balanced transfusion to patients with life‐threatening bleeding to improve survival. To provide the best care to patients with hemorrhagic shock in regions with reduced access to evacuation, blood preparedness must be ensured also on a municipal health care level. The primary aim of the Norwegian Blood Preparedness project is to enable rural hospitals, prehospital ambulance services, and municipal health care services to start early balanced blood tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 30 publications
0
23
0
1
Order By: Relevance
“…At this time, the use of cold-stored whole blood is considered a best practice by the US military, in adult trauma centers in the United States, and internationally. 43,[54][55][56] The benefits and risks of LTOWB compared with component therapy are summarized in Table 1. 45,50,51,53,57,58 Current data support that LTOWB is a safe, efficient, and feasible tool in pediatric trauma resuscitation and may also improve clinical outcomes.…”
Section: Whole Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…At this time, the use of cold-stored whole blood is considered a best practice by the US military, in adult trauma centers in the United States, and internationally. 43,[54][55][56] The benefits and risks of LTOWB compared with component therapy are summarized in Table 1. 45,50,51,53,57,58 Current data support that LTOWB is a safe, efficient, and feasible tool in pediatric trauma resuscitation and may also improve clinical outcomes.…”
Section: Whole Bloodmentioning
confidence: 99%
“…Hanna et al, 53 in an analysis of more than 8,000 patients in the Trauma Quality Improvement database, reported that LTOWB was independently associated with reduced 24-hour mortality, in-hospital mortality, and major complications in adults with traumatic bleeding. At this time, the use of cold-stored whole blood is considered a best practice by the US military, in adult trauma centers in the United States, and internationally 43,54–56 . The benefits and risks of LTOWB compared with component therapy are summarized in Table 1 45,50,51,53,57,58 …”
Section: Whole Bloodmentioning
confidence: 99%
“…This article reviews the literature on adult and pediatric applications of LTOWB with a focus on North America, as experience in other geographic areas has been published elsewhere. 3,4 It will also examine the use of LTOWB from vein to vein, starting at the blood center, then moving into the field, and finally into the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Blodprodukter til bruk ved eventuelle militaere operasjoner i Norge eller ved bruk av norske militaere styrker til operasjoner utenfor Norge må produseres av sivile blodbanker i Norge. Vandrende blodbanker er en nødløsning der tilstrekkelig tilgang på blodprodukter er truet av logistiske årsaker, men vil, som Nissen-Meyer og medforfattere påpeker, gi en svaert volummessig begrenset effekt (3,18,19).…”
Section: «Balansert Transfusjon Med Bruk Av Komponenter Krever Tre Te...unclassified